Case report: Additional variants induced sudden cardiac death among pediatric ACM with DSG2 homozygous mutant genotype: a report of three cases - Wei, Meng; Li, Yifei; Liu, Xiaoliang; Zhou, Kaiyu; Qiu, Yu; Liu, Lei; Huang, Lili; Liu, Zhongqiang (Frontiers in Genetics, 2024)
Background: Mutations in genes encoding desmosomal proteins are the leading cause of arrhythmogenic cardiomyopathy (ACM). The majority of the inherited ACM cases demonstrate autosomal dominant genotype. Several cases with the homozygous DSG2 c.1592T>G (p.F531C) variant genotype demonstrate adverse clinical outcomes, but the roles of associated genetic mutations are not clear. In this report, we describe three ACM cases with the homozygous DSG2 c.1592T>G (p.F531C) variant genotype combined with additional heterozygous cardiomyopathyrelated genetic mutations that cause aggravated clinical manifestations and worse clinical outcomes.The three reported probands demonstrated similar clinical presentations such as heart failure, cardiac enlargement, and lethal arrhythmias. All of them experienced sudden cardiac death (SCD) before undergoing implantable cardioverter defibrillator (ICD) or heart transplantations. Whole-exome sequencing analysis demonstrated that the three patients inherited the homozygous DSG2 c.1592T>G (p.F531C) variant. Furthermore, probands I, II, and III also inherited additional heterozygous cardiomyopathy-associated mutations, including DSP c.7883T>C, SCN5a c.3577C>T, or MYH7 c.427C>T, respectively. These variants were confirmed as pathogenetic variants. A systematic review of all the reported ACM cases with the homozygous DSG2 variants suggested that the additional genetic mutations contributed to the early age onset of ACM and lethal cardiac events.In conclusion, we report three rare cases of ACM with the same homozygous DSG2 variant in combination with additional heterozygous mutations in cardiomyopathy-associated genes. A systematic review of all the ACM cases with homozygous DSG2 variants demonstrated that the additional genetic variants contributed to the aggravated clinical manifestations and worse clinical symptoms of the ACM patients because of homozygous DSG2 mutations, including early disease onset and lethal cardiac events. Our data suggested that comprehensive genetic evaluation should be performed to identify any potential additional pathogenic variants that may significantly influence the clinical prognosis and outcomes of patients with ACM. The knowledge of underlying molecular mutations would be useful in designing better therapeutic strategies for ACM patients with multiple genetic mutations.